2022
DOI: 10.3389/fmed.2022.986218
|View full text |Cite
|
Sign up to set email alerts
|

State of the art and future directions in assessing the quality of life in rare and complex connective tissue and musculoskeletal diseases

Abstract: BackgroundAs chronic conditions, rare and complex connective tissue and musculoskeletal diseases (rCTDs) significantly affect the quality of life generating an impact on the physical, psychological, social, and economic dimensions of the patients’ lives, having implications on the family, changing the lifestyle and interpersonal relationships. Traditionally, generic and disease-specific measures for Quality of Life (QoL) provide valuable information to clinicians since QoL affects healthcare services utilizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 77 publications
0
4
0
1
Order By: Relevance
“…Darbingo amžiaus asmenys dažniausiai patiria kaklo ir apatinės nugaros dalies skausmus, vyresni -įvairias sąnarių patologijas [1]. Dėl nuolatinio varginančio skausmo paveikiama asmens gyvenimo kokybė fizinėje, psichosocialinėje ir ekonominėje srityje, nukenčia šeiminiai ir tarpasmeniniai santykiai [3,4], o ilgainiui kaulų -raumenų sistemos sutrikimai sąlygoja žmogaus negalią [3].…”
Section: įVadasunclassified
“…Darbingo amžiaus asmenys dažniausiai patiria kaklo ir apatinės nugaros dalies skausmus, vyresni -įvairias sąnarių patologijas [1]. Dėl nuolatinio varginančio skausmo paveikiama asmens gyvenimo kokybė fizinėje, psichosocialinėje ir ekonominėje srityje, nukenčia šeiminiai ir tarpasmeniniai santykiai [3,4], o ilgainiui kaulų -raumenų sistemos sutrikimai sąlygoja žmogaus negalią [3].…”
Section: įVadasunclassified
“…99 Several studies have reported a poorer health-related quality of life in patients with myositis compared with the general population. 46,[95][96][97][100][101][102][103][104][105][106][107][108][109] In 2016, a systematic review of 10 studies including 654 patients with IIM on healthrelated quality of life demonstrated a significantly impaired health-related quality of life in all subsets of IIM compared with the general population. 95 Disease activity, disease damage and chronic disease course were associated with poorer health-related quality of life.…”
Section: Improving Psychological Outcomesmentioning
confidence: 99%
“…In selecting tools as measures of value, healthcare professionals are encouraged to identify evidence‐based instruments with high reliability, validity, and internal consistency 18 . Survey instruments can be used to characterize the quality of life, patient satisfaction, and provider satisfaction 19,20 . When attempting to demonstrate value from the healthcare or payer perspectives cost‐effectiveness and cost avoidance designs may be preferred although a quality improvement, such as improvement in clinical outcomes and improvement in vaccination rates are desirable components of value 16,17 .…”
Section: Perspective Value Sample Measures Study Designsmentioning
confidence: 99%
“…18 Survey instruments can be used to characterize the quality of life, patient satisfaction, and provider satisfaction. 19,20 When attempting to demonstrate value from the healthcare or payer perspectives cost-effectiveness and cost avoidance designs may be preferred although a quality improvement, such as improvement in clinical outcomes and improvement in vaccination rates are desirable components of value. 16,17 The provider perspective of value can be demonstrated through survey instruments and collaborative/interprofessional practice scales, such as the Assessment of Interprofessional Team Collaboration Scale (AITCS) or Team Decision Making Questionnaire (TDMQ).…”
mentioning
confidence: 99%